Mental health recovery: A review of the peer-reviewed published literature. Issue 1 (February 2017) - Jacob, Sini; Munro, Ian; Taylor, Beverley Joan; Griffiths, Debra
Summary: The concept of mental health recovery promotes collaborative partnership among consumers, carers and service providers. However views on mental health recovery are less explored among carers and service providers. The aim of this review was to analyse contemporary literature exploring views of mental health consumers, carers and service providers in relation to their understanding of the meaning of mental health recovery and factors influencing mental health recovery. The literature review questions were: How is mental health recovery and factors influencing mental health recovery viewed by consumers, carers and service providers? What are the differences and similarities in those perceptions? How can the outcomes and recommendations inform the Australian mental health practices? A review of the literature used selected electronic databases and specific search terms and supplemented with manual searching. Twenty-six studies were selected for review which included qualitative, mixed method, and quantitative approaches and a Delphi study. The findings indicated that the concept of mental health recovery is more explored among consumers and is seldom explored among carers and service providers. The studies suggested that recovery from mental illness is a multidimensional process and the concept cannot be defined in rigid terms. In order to achieve the best possible care, the stakeholders require flexible attitudes and openness to embrace the philosophy.